Towards an in-situ measurement of wave velocity in buried plastic water distribution pipes for the purposes of leak location - Almeida, Fabrício C.L. [UNESP]; Brennan, Michael J. [UNESP]; Joseph, Phillip F.; Dray, Simon; Whitfield, Stuart; Paschoalini, Amarildo T. [UNESP] (Elsevier, 2015)
Water companies are under constant pressure to ensure that water leakage is kept to a minimum. Leak noise correlators are often used to help find and locate leaks. These devices correlate acoustic or vibration signals from sensors which are placed either side the location of a suspected leak. The peak in the cross-correlation function of the measured signals gives the time difference between the arrival times of the leak noise at the sensors. To convert the time delay into a distance, the speed at which the leak noise propagates along the pipe (wave-speed) needs to be known. Often, this is estimated from historical wave-speed data measured on other pipes obtained at various times and under various conditions, or it is estimated from tables which are calculated using simple formula. Usually, the wave-speed is not measured directly at the time of the correlation measurement and is therefore potentially a source of significant error in the localisation of the leak. In this paper, a new method of measuring the wave-speed in-situ in the presence of a leak, that is robust and simple, is explored. Experiments were conducted on a bespoke large scale buried pipe test-rig, in which a leak was also induced in the pipe between the measurement positions to simulate a condition that is likely to occur in practice. It is shown that even in conditions where the signal to noise ratio is very poor, the wave-speed estimate calculated using the new method is less than 5% different from the best estimate of 387 m s-1.